The Impact of Online Loan Traps (P2P Lending Fintech) on Divorce Rates: A Maqashid al-Sharia Approach to Protecting Family Economic Resilience - Muhammad Syakir Al Kautsar; Nurul Mahmudah; Muhammad Rifqi Hidayat (Nuban Jagadhita Centre, 2026)
Objective: This study aims to analyze the relationship between online loan debt, household economic stress, and vulnerability to divorce from the perspective of maqashid syariah. It seeks to explain how the rapid expansion of digital lending services influences family economic resilience and social well-being within the framework of Islamic economics. Method: This study employs a descriptive qualitative approach based on a literature review using content analysis. Data were sourced from regulations, national statistical reports, academic articles, fatwas, and court rulings published online. The analysis was conducted by identifying patterns of argumentation, empirical trends, and conceptual relationships between the development of P2P lending fintech, family economic dynamics, and economic factors contributing to divorce. Relevant literature was further examined through the lens of contemporary maqashid syariah to understand the broader social implications of digital financial practices. Results: The study indicates that ease of access, fast disbursement processes, and low administrative barriers encourage repeated use of digital loans, particularly among households with unstable incomes and limited financial literacy. This pattern has the potential to trigger debt accumulation, financial pressure, psychological stress, a decline in the quality of communication between partners, and an increase in domestic conflict, all of which are associated with heightened vulnerability to divorce. The findings also suggest that excessive dependence on online borrowing may weaken household financial sustainability and undermine long-term family stability. Implication: This study underscores the importance of consumer protection policies that not only focus on cost transparency and data security but also include assessments of repayment capacity, strengthened financial literacy, responsible lending practices, and measures to safeguard family economic resilience. Novelty: This study integrates P2P lending fintech research with studies on family resilience through the lens of Jasser Auda’s contemporary maqashid syariah systems perspective. This study expands the discourse on Islamic economics by positioning the protection of wealth (hifz al-mal) and the protection of family/progeny (hifz al-nasl) as a unified systemic framework for assessing the impact of digital financial innovations.